What predicts incarceration among urban adults with co-occurring severe mental illness and substance use disorders? - Luciano, Alison (Psychiatr Serv, 2014)
OBJECTIVE: People with a severe mental illness and co-occurring substance use disorder (i.e., co-occurring disorders) living in urban areas experience high rates of incarceration. This study examined socio-demographic, clinical, economic, and community integration factors as predictors of incarceration among people with co-occurring disorders. METHODS: The sample came from secondary data from a randomized controlled trial of assertive community treatment versus standard case management, in which researchers interviewed 198 people with co-occurring disorders from two urban mental health centers in Connecticut at baseline and every six months for three years. Researchers tracked incarceration, clinical engagement and status, employment, living situation, social relationships, and substance use. Bivariate analyses and logistic regression analyses compared individuals who were ever-incarcerated and never-incarcerated during the study period. RESULTS: The overall incarceration rate was 38% during the study period. In multivariate analyses, previous incarceration predicted incarceration during the study (OR = 3.26), while friendships with non-substance users (OR = 0.19), and substance use treatment engagement (OR = 0.60) were associated with reduced likelihood of incarceration. CONCLUSIONS: Positive social relationships and engagement in treatment for substance use are promising service and policy targets to prevent incarceration in this high-risk population.